Application of Mathematical Models in Creating Optimal Strategies to Reduce Home Ownership Credit Costs - Alifah, Fathin; Kurniasih, Kayla Nurul (iora, 2025)
Home Ownership Credit (KPR) is one of the important financing options for people who want to own a home. However, the total amount to be paid during the loan period is high, which is why for many borrowers this study aims to apply mathematical models to develop optimal strategies to reduce the overall mortgage entry costs. This study uses the annuity concept to model installment payments by considering factors such as interest rate, term, and payment frequency. The model also considers repayment scenarios that include early repayment options to reduce long-term interest costs. Simulation results show that by choosing a shorter period and using early payments in certain periods, significant overall cost savings can be achieved. In addition, although variable interest rates are riskier, they have been shown to offer greater savings potential than fixed interest rates under certain economic conditions. The conclusion of this study is that the application of an optimal payment strategy through a mathematical approach can significantly reduce total mortgage costs and provide long-term benefits to borrowers.